Aligned 2D CuSCN nanosheets: a high performance field emitter. Issue 76 (29th July 2016) - Patil, Girish P.; Baviskar, Prashant K.; Bagal, Vivekanand S.; Ladhe, Ravindra D.; Deore, Amol B.; More, Mahendra A.; Sankapal, Babasaheb R.; Chavan, Padmakar G.
Abstract : Aligned 2D CuSCN nanosheets were grown by a simple, low cost and room temperature SILAR technique. The field emission properties of aligned 2D CuSCN nanosheets were studied in detail. Abstract : A low turn-on field of 2.4 V μm −1 is observed for the emission current density of 10 μA cm −2 from aligned copper thiocyanate (CuSCN) nanosheets. The observed low turn-on field is found to be superior to that of inorganic semiconducting and carbon based nanomaterials reported in the literature. The field emission current stability for the preset value of 1 μA over the period of 3 h is found to be better. Aligned CuSCN nanosheets were grown on fluorine doped tin oxide (FTO) coated glass substrates by a simple, low cost Successive Ion Layer Adsorption and Reaction (SILAR) technique at room temperature. Detail characterization of aligned CuSCN nanosheets has been carried out using Field Emission Scanning Electron Microscopy (FESEM), X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM). To the best of our knowledge this is the first report on the field emission studies of aligned CuSCN nanosheets. The simple and inexpensive synthesis route coupled with superior field emission make the present emitter suitable for micro/nano electronic devices.